Pengaruh Mentoring Kajian Dhuha Qatulistiwa Islam Unit Kegiatan Kerohanian Terhadap Akhlak Mahasiswa Universitas Negeri Padang - Rihha Datul Aisy; Sulaiman Sulaiman (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to determine the implementation of moral development in the mentoring of the Dhuha study, then to determine the effect of mentoring in the dhuha study on the results of the moral development of Universitas Negeri Padang students. And to find out the effectiveness of the implementation of mentoring in the study of dhuha on the results of moral development of Padang State University students. The type of research used is field research (field research) with a quantitative research approach. The results of this study explain that the mentoring of the Islamic Dhuha Qatulistiwa Study has an influence on the morals of Universitas Negeri Padang students. It can be seen from the simultaneous significant test that the calculated F value = 23,800 with an F table value of 3.94 with a significance level of confidence 0.05, thus the Fcount value 23,800> F-table 3.94, with a significance level of 0.000, it means that there is a significant effect between the Dhuha Study Mentoring variable (X) and the Student Morals variable (Y). So there is a positive and significant relationship between the mentoring of the Islamic Dhuha Qatulistiwa Study on the Morals of Universitas Negeri Padang.